A Combined Clearing Model of Electric Energy, Inertia, and Primary Frequency Regulation Considering Emergency Interruptible Load Service - ZHU Lan, ZHANG Xuehan, TANG Longjun, QIU Nianhang, TIAN Yingjie (Shanghai Jiaotong Daxue xuebao)
The ever-increasing proportion of new energy units has led to prominent frequency safety issues in the power system. In order to avoid serious accidents after the system encounters large disturbance, it is necessary to purchase inertia and primary frequency regulation auxiliary services and integrate rapid response resources such as emergency interruptible load service into the system. Therefore, based on a review of the domestic and foreign inertia ancillary service market, the frequency safety constraints considering the emergency interruptible load service are derived, and a joint clearing model of electric energy, inertia, and primary frequency regulation auxiliary services is proposed, considering emergency interruptible load service. Then, the model is transformed into a mixed integer second-order cone programming model for optimization. Finally, the effectiveness of the model is verified based on a numerical example, and the influence of the frequency safety constraints on the system clearing results is discussed.